Ordinance No. 160, § 10: An Ordinance Defining Offenses Against the Peace and Good Order of the City of Caldwell, and Providing Punishment Therefore, in The Caldwell Tribune, May 27, 1910, at 2 (Caldwell, Idaho) - (:unkn) unknown (My University, 1910)
§ 10: Prohibited any person from carrying any slingshot, or carrying concealed any deadly weapon without permission from the mayor. Violators fined not exceeding one hundred dollars.
Keywords: CARRY - CONCEALED